PENGEMBANGAN APLIKASI PERMAINAN SCRABBLE DUA BAHASA MENGGUNAKAN JAVA - Fajar Masya; Elvina Elvina (Bina Nusantara University, 2010)
Game applications are favored by many computer users. The population of Indonesia, especially common people do not like playing games in a foreign language. Yet such games can be a fun learning media for foreign languages , especially English. Hence, we developed a game application using the concept of the game Scrabble. The design of this application uses a waterfall methodology, with application design modeling with UML diagrams (Unified Modelling Language) including Use Case Diagram, Activity Diagram, Statechart Diagram, Class Diagram and Sequence Diagram. In the implementation phase, Blue J software used to build the interface using the Java Development Kit (JDK) version jdk1.6.0_02 as the executor, as well as using the command prompt to call the results of execution. Tests on gaming applications are performed using the Black Box and White Box method. The product of this development is a single player game application, which uses two language options.Keywords: game applications, Scrabble, waterfall software engineering methodologies, UML (Unified Modeling Language), Java Programming.